The long non-coding RNA ZFAS1 promotes colorectal cancer progression via miR200b/ZEB1 axis - Salman, Islam T.; Abulsoud, Ahmed I.; Abo-Elmatty, Dina M.; Fawzy, Amal; Mesbah, Noha M.; Saleh, Samy M. (Pathology, research and practice, 2023)
Colorectal cancer (CRC) is a common tumor worldwide. CRC is influenced by several types of miRNAs and long non-coding RNAs. This study aims to evaluate the correlation of lncRNA ZFAS1/ miR200b/ ZEB1 protein with presence of CRC. Quantitative real-time polymerase chain reaction was used to measure serum expression of lncRNA ZFAS1 and microRNA-200b in 60 CRC patients and 28 control subjects. ZEB1 protein in serum was measured by ELISA. Lnc ZFAS1 and ZEB1 were up-regulated in CRC patients in compare to control subjects while miR-200b was down-regulated. There was a linear correlation between ZAFS1 expression and miR-200b and ZEB1 in CRC. ZFAS1 is a key player of CRC progression and could be a potential therapeutic target by sponging miR-200b. In-addition the association between ZFAS1, miR-200b and ZEB1 highlights their potential value as a novel diagnostic biomarker in human CRC. [Display omitted]